Why Did Central Banks Intervene in the EMS? The Post-1993 Experience - Peter Brandner; Harald Grech (Austrian Institute of Economic Research (WIFO), 2002)
In this paper, we present stylized facts of exchange rate and intervention behavior in the Exchange Rate Mechanism I (ERM I), in particular in light of the recent literature on multilateral target zone models. We estimate bilateral exchange rate distributions of the maximum spot rate deviations of six ERM-currencies explicitly taking the multilateral setting of the ERM I into account. In a further analysis, we estimate short term reaction functions for the Banque de Belgique, the Danmarks Nationalbank, the Banco d'Espa\~na, the Banque de France, the Central Bank of Ireland and the Banco de Portugal by applying a Tobit analysis. The period under review ranges from August 1993 to April 1998. Daily exchange rate and intervention data are used. The exchange rate position in the band (deviation of the DEM-spot rates from the DEM-central parity) significantly induces intervention activity. There is less evidence that changes in volatility trigger central bank intervention.
Keywords: E58; F31; F33; 330; Foreign Exchange Intervention; European Monetary System; Central Bank's Reaction Function; Wechselkurspolitik; Europäisches Währungssystem; Schätzung; Taylor-Regel